Theoretical frameworks of self-efficacy in collaborative science learning practices: A systematic literature review - Reni Marlina; Hadi Suwono; I. Ibrohim; Chokchai Yuenyong; H. Husamah; H. Hamdani (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Theoretical framework is one of the main parts of the research paper, so that researchers are expected to be able to determine the relevant theory that underlies their research. The purpose of conducting this systematic literature review (SLR) is to review of theoretical framework, compare, and describe various theoretical research frameworks in an investigative manner on the theme of self-efficacy in collaborative science learning that underlies publications in Scopus indexed journals in the last ten years. In this regard, we used the phrase "self-efficacy in collaborative science learning" on the disbursement menu in the Scopus database and found 711 articles. There were 63 articles that met the criteria for analysis. The inclusion and exclusion model used is PRISMA. The newly discovered aspects consist of community of practice, professional learning community, and reflection, which are as a result of the development of a theory of change and a theory of instruction constructed from theoretical frameworks in the recent collaborative science learning practices literature. Therefore, the development of this theory can be considered as a theoretical basis for developing the self-efficacy of prospective science teachers in collaborative learning in the future. The purpose of conducting this systematic literature review (SLR) is to review, compare, and describe various theoretical research frameworks in an investigative manner on the theme of self-efficacy in collaborative science learning that underlies publications in Scopus indexed journals in the last ten years. In this regard, we used the phrase "self-efficacy in collaborative science learning" on the disbursement menu in the Scopus database and found 711 articles. There were 63 articles that met the criteria for analysis. The inclusion and exclusion model used is PRISMA. The newly discovered aspects consist of community of practice, professional learning community, and reflection, which are as a result of the development of a theory of change and a theory of instruction constructed from theoretical frameworks in the recent collaborative science learning practices literature. Therefore, the development of this theory can be considered as a theoretical basis for developing the self-efficacy of prospective science teachers in collaborative learning in the future.